Platelet and coagulation disorders in newly diagnosed patients with pulmonary arterial hypertension. (4th July 2019) - Vrigkou, Eleni; Tsangaris, Iraklis; Bonovas, Stefanos; Kopterides, Petros; Kyriakou, Elias; Konstantonis, Dimitrios; Pappas, Athanasios; Anthi, Anastasia; Gialeraki, Argyri; Orfanos, Stylianos E.; Armaganidis, Apostolos; Tsantes, Argyrios
Abstract: There is a complex and not fully elucidated association between pulmonary arterial hypertension (PAH) and coagulation disorders. The goal of this study was to evaluate platelet function, coagulation and fibrinolysis in PAH patients at diagnosis, before PAH-specific treatment initiation. We enrolled 20 healthy controls and 30 PAH patients (20 with connective tissue disease (CTD-PAH) and 10 idiopathic (iPAH)). None of the participants was on any antiplatelet or anticoagulation therapy. Blood samples from PAH patients were collected during the initial right heart catheterization. All subjects were assessed with platelet function analyzer-100 (PFA-100), epinephrine (Epi) and ADP-induced light transmission aggregometry (LTA), thromboelastometry (ROTEM) and endogenous thrombin potential (ETP). Our results showed that Epi and ADP-LTA values were significantly lower in newly diagnosed PAH patients compared to controls. Disaggregation was present in 73% of patients, a characteristic not seen in healthy individuals. In ROTEM assay, CT and CFT measurements were significantly higher and a angle lower compared to controls. ETP testing revealed significantly reduced outcomes in AUC, Cmax and Tmax. When CTD-PAH and iPAH patient groups were compared, iPAH ADP-LTA values were significantly decreased compared to CTD-PAH. In conclusion, newly diagnosed PAH patients presented with decreased platelet aggregation, clot propagation and thrombin generation, along with delayed initiation of the coagulation process. These hemostatic deficits could indicate an "exhaustion" of the coagulation process that could be caused by endothelial dysfunction and chronic activation of the procoagulant pathways. Further studies are warranted to confirm these laboratory findings and assess their potential clinical significance.